Electron and Photon Interactions with Bio(Related) Molecules - Ferreira da Silva, Filipe (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint compiles several studies on radiation interactions with biomolecules. The fragmentation induced by slow electron and electron scattering processes are described, and the induced processes by UV radiation are characterised. The present Special Issue offers complementary studies on radiation induced by photons and electrons in biological (and related) target molecules. The present collection provides important insights on radiation physics and chemistry and the advances in knowledge in these areas.